Root exudates and plant secondary metabolites of different plants enhance polychlorinated biphenyl degradation by rhizobacteria. Issue 2 (2nd April 2016) - Pino, Nancy J.; Muñera, Luisa M.; Peñuela, Gustavo A.
ABSTRACT: Polychlorinated biphenyls (PCBs) are toxic and persistent compounds that are difficult to break down and biodegrade. Plant secondary metabolites (PSMs) on root exudates can act as inducers of the biphenyl catabolic pathway, enhancing PCB biodegradation. In this study, the authors evaluated the effect of root exudates and PSMs obtained from Avena sativa, Brachiaria decumbens, Medicago sativa, and Brassica juncea on the biodegradation of PCB 44, PCB 66, PCB 118, PCB 138, PCB 153, PCB 170, and PCB 180 by a microbial consortium isolated from the rhizosphere of plants grown on soil contaminated with Aroclor 1260. Microorganisms were identified as Pseudomonas sp. and Stenotrophomonas sp. based on their 16S rRNA sequence. The plant root exudates increased the degradation percentage of PCB 44, PCB 66, and PCB 118, which were used as carbon source by the microorganisms. Flavanone, flavone, isoflavone, 7-hydroxyflavanone, 7-hydroxyflavone, and 6-hydroxyflavone were the PSMs identified in the root exudates, which increased the degradation percentage of all seven PCB congeners; they were also used as growth substrates by microbial consortium. These results showed the importance of the interaction between plants and microorganisms for achieving the removal of persistent pollutants such as PCBs from soil.